Literature review of judgment and decision in auditing - Nguyễn Thị Thu Hiền (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kinh tế và Quản trị kinh doanh, 2021)
Judgment and Decision Marking research (JDM) in auditing is becoming more critical in general judgment theory, in auditing theory, and in auditing practice. This paper synthesizes the theory of JDM in auditing so that it provides an overview of this literature and provides suggestions for future researches. Based on a list of reviewed papers on JDM in auditing until 2010 by (Mala & Chand, 2015), this article has included relevant researches from 2010 to 2019 published in ten auditing and accounting journals. By using the content analysis method to analyze 244 related selected papers, this article has synthesized JDM literature in auditing over nearly half a century by topics of people, tasks, and environment through each period. The paper’s finding provides suggestions for future studies on the factors that influence auditor judgment and decision-making performance. In addition, the article also summarizes the strengths and limitations of the laboratory method used mainly in JDM research in auditing.